Teen spirit [videorecording (DVD)] - Minghella, Max, 1985-; Fanning, Elle, 1998-; Buric, Zlatko, 1953-; Grochowska, Agnieszka, 1979- (Universal Pictures Home Entertainment, 2019)
Violet is a shy teenager who dreams of escaping her small town and pursuing her passion for singing. With the help of an unlikely mentor, she enters a local singing competition that will test her integrity, talent, and ambition. Driven by a pop-fueled soundtrack, it is a visceral and stylish spin on the Cinderella story.